PENERAPAN MODEL PEMBELAJARAN INKUIRI UNTUK MENINGKATKAN HASIL BELAJAR IPA SISWA KELAS IV SD NEGERI 6 KADUR - Misyani, Misyani; Lazim N, Lazim N; Antosa, Zairul (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract: This research is motivated by the result of low science student learning and there are still many students who have not reached the minimum completeness criteria is 65. From 21 students only 9 students (42,86%) reaching minimum completness criteria and 12 students (57, 14%) did not achieve the minimum mastery criteria. This research is a classroom action research conducted on the fourth grade students of SDN 6 Kadur Kecamatan Rupat Utara. Research Instrument consists of Learning Device which used in this research based on Education Unit Level Curriculum or known as Curriculum 2006. Learning tools consist of syllabus, Learning Implementation Plan, student worksheet and observation sheet. The first meeting of cycle I to the activity of the teacher that is the average of teacher activity observed in cycle II has increased compared to cycle I.In the first meeting of the first cycle of teacher activity average of 71.42% in the good category, at the second meeting the average teacher activity increased to 82.14% in very good category. At the third meeting of cycle II the average teacher activity 85.71% with very good category and at the fourth meeting with an average of 96.42% activity in the category of Very Good.The first meeting of the first cycle of student activity average 64.28% with sufficient category, at the second meeting the average activity increased to 75% with good category. In the third meeting of cycle II the average student activity 82.14% in very good category and at the fourth meeting increased compared to the previous meeting with an average of 96.42% student activity with very good category. Student learning outcomes after preliminary data of students who are above the Criteria Completed minimum only 9 people (42.86%) after cycle I increased up to 15 people (28.56%) after the second cycle increased more up to 20 people (23, 81%) as well as the average value obtained by students classically in the initial data was only 42.86 and after the first cycle increased by an average of 71.42 and in the second cycle increased more up to 95.23. This means that the classic value obtained by students has been above the KKM that has been set.Keywords: inquiry learning model, learning outcomes of science